Mortality and health spending during the first year of the COVID-19 pandemic: Comparing central, eastern and western Europe - Agata Kliber; Elżbieta Rychłowska-Musiał (Comparative Economic Research. Central and Eastern Europe, 2023)
The article shows the relationships between the COVID and non-COVID deaths during the first year of the pandemic, compared with the stringency of restrictions imposed and the compulsory spending on healthcare. We compare these relationships among European countries, analysing weekly data and applying cointegration models. Regarding the pandemic's intensity, we split the period into two: March - August 2020 and September 2020 - February 2021. We find that, most often, if there was a relationship between the stringency index and COVID or non-COVID mortality, it was usually positive and mortality driven. That suggests that although the governments tailored the restrictions to the growing mortality rate, they were unable to control the pandemic. No relationships, or negative ones, were most often found in these countries where the spending on healthcare was the highest (i.e., Northern and Western European countries). The biggest weekly changes in non-COVID deaths during the second sub-period were observed in the Central and Eastern European countries, where government healthcare expenditures per capita are the lowest.
Keywords: I14; I15; I16; H51; 330; COVID mortality; Stringency Index; non-COVID mortality; Johansen test; cointegration; healthcare spending